Analysis of the impact and compression after impact behavior of tufted laminated composites. (15th January 2018) - Martins, A.T.; Aboura, Z.; Harizi, W.; Laksimi, A.; Khellil, K.
Abstract: The effect of trough-the-thickness reinforcement by tufting on impact and after impact behavior of woven carbon fiber composites is investigated. The density and angle of the carbon fiber threads during tufting process were varied to achieve better results on damage tolerance. The samples were submitted to out-of-plane impact with two different energies to compare their response under loading. Then, they were analyzed by ultrasonic C-Scan technique in order to evaluate the damaged zone. Further, compression after impact (CAI) assisted by acoustic emission and Digital Image Correlation compared the compressive strength and materials response according to their tufting parameters. Also, compression before impact (CBI) were performed to evaluate the in-plane properties of the tufted composites. The transversal tufting reinforcement achieved the best results when compared to angular and non-tufted laminate composites. Moreover, when increasing the tufting density, the damaged area is decreased and the ultimate compressive strength improved. Tufting reinforcements were found to decrease the damage area up to 4 times (transversal tufting) when compared to non-tufted laminates. Additionally, the residual ratio (CAI/CBI) increased up to 30% and 28% for the transversal and angular reinforcements respectively in comparison to the reference.